Health-promoting services provided in pharmacies: A systematic review - Arash Shirdel; Abolghasem Pourreza; Amin Daemi; Batoul Ahmadi (Wolters Kluwer Medknow Publications, 2021)
Pharmacies are a major component of health systems and a major part of health service provision. This study aimed at identifying and introducing the potentials of pharmacies in health promotion. This was a systematic review that searched PubMed, Web of Science, Science Direct, SID, Magiran, and IranMedex from February 1990 to September 2018 for related materials. The main search keywords were (pharmacy services), (community pharmacy services), (retail pharmacy services), (pharmacy practice intervention). Inclusion was limited to those papers that discussed the health-promoting services provided in the pharmacies. The quality of included papers was assessed by the Critical Appraisal Skills Program checklists. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses chart was followed in all stages of the study. Of the 4156 papers retrieved, 18 met the inclusion criteria and included in the analysis. Study findings were categorized into three main categories: Health and prevention services, services related to treatments, and the awareness about the pharmacies' functions. The health and prevention category consisted of education, vaccination, screening and prevention of diseases, family planning, blood pressure monitoring, quitting smoking, limiting alcohol, and weight management. The treatment-related services consisted of adherence to medication, medication consultation, minor pains, and emergency medical services. Pharmacies can provide a wide variety of services besides the medications. Purposeful development of the services provided in the pharmacies and involving them in an extended array of services may accelerate the health promotion activities of the health system and result in improved quality of life and decreased costs. To do so, the legal, educational-skill, and pricing challenges should be resolved.